Unholy Wars: Afghanistan, America, and International Terrorism by John K. Cooley (Sterling, VA: Pluto Press, 2000. 299 pages.) (American Journal of Islam and Society, 2003)
Reading this book is a lot like trying to eat undercooked meat – there is proteinin there, but it is flavorless and tedious. You can chew and chew, but youjust cannot bring yourself to swallow it. The author presents his case with anauthoritative tone, stuffing each paragraph with names, dates, and historicaldata, but a closer look reveals the use of manipulative language that stringstogether half-truths and repeated insinuations with conclusions that do notdirectly relate to the given evidence. The “Acknowledgements” mention thatthe author has important friends in media and politics, yet his credentials(e.g., for whom he is working, or what his political motivations are) are notgiven. This is a serious weakness.Even more serious is his clear contempt for Islam, for he makes no genuinedistinction between Muslims’ desire for self-rule based upon their beliefsystem (often called “Islamism”) and terrorism. The CIA’s use of Muslimlives to advance American corporate interests is taken for granted, whileMuslims are portrayed as untrustworthy imbeciles or ungrateful servants.Such mainstream and moderate organizations and intellectuals as TablighiJamaat, Jamaat Islami, Maududi of Pakistan, and Hassan al-Turabi of Sudanare given as examples of dangerous extremism. American terrorism againstIraq, Sudan, and Afghanistan, and its support of Israel, are unquestioned asbeing justified, noble, and necessary, while any attack on western interests orAmerican lives is described with emotionally loaded terms. The only seriouscriticism of the United States is that it ever trusted Muslims as allies ...